2016
DOI: 10.4238/gmr.15038632
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serum level of chemokine (C-C motif) ligand 18 and poor prognosis in breast cancer

Abstract: ABSTRACT. In this study, we investigated the correlation between serum chemokine (C-C motif) ligand 18 (CCL-18) and the prognosis as well as clinical characteristics of breast cancer. Blood samples from 207 breast cancer patients, 126 individuals with benign breast tumors, and 93 healthy women were collected. Serum CCL-18 expression was detected by enzyme-linked immunosorbent assay. Mann-Whitney's U tests were carried out to analyze the relationship between serum CCL-18 and clinicopathological variables. The K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…27 CCL18 acts as a biomarker, 9,10 associated with poor prognosis as an independent factor in cancer patients. 11,12 In this study, in consistence with previous results, 21 we found that CCL18 high expression had an association with tumor recurrence, but had no correlation with OS in patients with GC. Multivariate analysis revealed CCL18 as an independent prognostic factor of tumor recurrence in patients with GC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…27 CCL18 acts as a biomarker, 9,10 associated with poor prognosis as an independent factor in cancer patients. 11,12 In this study, in consistence with previous results, 21 we found that CCL18 high expression had an association with tumor recurrence, but had no correlation with OS in patients with GC. Multivariate analysis revealed CCL18 as an independent prognostic factor of tumor recurrence in patients with GC.…”
Section: Discussionsupporting
confidence: 90%
“…5 Some studies show that the expression of CCL18 is increased in diffuse large B-cell lymphoma, 6 advanced breast cancer, 7 and low-grade endometrial cancer. 8 In addition, the serum level of CCL18 is elevated in epithelial ovarian cancer 9 and bladder cancer, 10 acting as a potential biomarker in these patients, 9,10 and associates with poor prognosis as an independent factor in patients with breast cancer 11 and colorectal cancer. 12 Moreover, CCL18 is involved in promoting cell proliferation, epithelial–mesenchymal transition (EMT), invasion and metastasis and repressing cell apoptosis in lymphoma, 6 pancreatic ductal adenocarcinoma, 13 breast cancer, 14 and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wu et al 23 found that the serum level of CCL18 in patients with gastric cancer was obviously higher than that of the control group; Sun and his coauthors revealed that the elevated serum level of CCL18 was associated with worse prognosis in female patients with breast cancer. 9 Likewise, Plönes et al 24 also indicated that the level of serum CCL18 was increased in NSCLC patients and predicted a diminished survival time in adenocarcinomas. However, Yuan et al 13 found that a high CCL18 level was significantly correlated with a better overall survival in colorectal cancer patients, which we consider may be related to the tissue specificity of CCL18 expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that the level of CCL18 expression was significantly elevated in NSCLC tissues, which correlated with tumor stage and lymph node metastasis. 14 Similarly, numerous studies have shown that increased expression of CCL18 was observed in a variety of cancers and is associated with their clinical pathological features, including oral squamous cell carcinoma, 15 colorectal cancer, 13 ovarian cancer, 16 breast cancer, 9 bladder cancer, 17 and so on. Recently, Eriksson Hogling et al 18 showed that circulating and WAT-secreted CCL18 was correlated with such metabolic risk factors as insulin resistance and metabolic risk score in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation